2012
DOI: 10.1139/l2012-034
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of fibre-reinforced polymer reinforced concrete deep beams without web reinforcement

Abstract: This paper describes an experimental investigation to evaluate the shear strength and behavior of concrete deep beams reinforced with fibre-reinforced polymer (FRP) bars. A total of ten full-scale reinforced concrete beams without web reinforcement were constructed and tested in four-point bending. The test variables were the reinforcement ratio and the modulus of elasticity of the longitudinal reinforcing bars as well as the shear span to depth ratio. The test beams included five beams reinforced with glass F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 5 publications
4
37
0
Order By: Relevance
“…For this purpose, a database of 39 tests of deep beams with FRP reinforcement was collected from five experimental studies (Andermatt and Lubell 2013b;El-Sayed et al 2012;Farghaly and Benmokrane 2013;Latosh 2014;Mohamed et al 2014). Only test series that contained at least several relatively large beams, i.e., d > 300 mm, were selected to avoid the inherent scatter in smaller members.…”
Section: Modifications To the Original 2pkt Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a database of 39 tests of deep beams with FRP reinforcement was collected from five experimental studies (Andermatt and Lubell 2013b;El-Sayed et al 2012;Farghaly and Benmokrane 2013;Latosh 2014;Mohamed et al 2014). Only test series that contained at least several relatively large beams, i.e., d > 300 mm, were selected to avoid the inherent scatter in smaller members.…”
Section: Modifications To the Original 2pkt Approachmentioning
confidence: 99%
“…El-Sayed et al (2012) used CSA-S806-11 (CSA 2011) shear provisions to predict the shear strength of eight test specimens without web reinforcement and obtained experimental-to-predicted ratios with an average of 1.33 and a coefficient of variation (COV) of 12%. The code equations became less conservative as the stiffness of the longitudinal reinforcement decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous research studies, the basic effective parameters that affecting the shear capacity of FRP-RC beams are the width of web (b w ), effective depth of beam (d), shear span to depth ratio (a/d), concrete compressive strength (f c ′ ), longitudinal reinforcement ratio (ρ f ) and elastic modulus of FRP bars (E f ) [35,[45][46][47][48][49]. An experimental database of 138 test specimens failed in shear was obtained from different previous investigations [31,36,45,47,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. During the collection stage, specimens with shear span to depth ratios between 2.4 and 6.5 were included but deeper and slender beams were omitted from the database.…”
Section: Experimental Datamentioning
confidence: 99%
“…Different mechanical properties between FRP and conventional steel bars may affect the shear carrying mechanism in concrete beams. More rapid deterioration in shear can be observed in concrete beams longitudinally reinforced by steel rather than those reinforced by FRP due to the reduction shear resistance offered by un-cracked concrete, V c [9,10]. The shear resistance of FRP RC beams also influences by the size-effect and shear-span-to-depth ratios [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More rapid deterioration in shear can be observed in concrete beams longitudinally reinforced by steel rather than those reinforced by FRP due to the reduction shear resistance offered by un-cracked concrete, V c [9,10]. The shear resistance of FRP RC beams also influences by the size-effect and shear-span-to-depth ratios [10,11]. The experimental results on the ratios of the reinforcement indicated that the beams provided with stirrups and multiple layers of flexural reinforcement is recommended in order to resist the weak bend area of FRP stirrup cages [12].…”
Section: Introductionmentioning
confidence: 99%